Credit Where Credit Is Due: Data and Software in the Space Weather Community - S. K. Morley; H. Liu; B. A. Carter; J. L. Gannon; N. Lugaz (Space Weather)
Abstract This editorial aims to improve awareness of the current best practices in open research, and stimulate discussion on the practical implementation of AGU's data and software policy in key areas of space weather research. We also further aim to encourage authors to take additional steps to ensure clear credit to all contributors to the work, whether that is underlying data, key software, or direct contributions to the manuscript.